KEKERABATAN BAHASA KULAWI DAN BAHASA KAILI DI SULAWESI TENGAH - Siti Fatinah (Kantor Bahasa Sulawesi Tenggara, 2017)
Kaili dan Kulawi languages are related and predicted they descent from common ancestral language (proto-language). Their relation need to be proved in qualitative and quantitative methode. This research applied and those methode in describing the relation between the languages. The aim of the research is describing the relation in qualitative and quantitative method. The data is based on questions and interviews which are elaborated into questionnaire with 200 Swadesh list and 873 culture vocabularies. The paper is applied method of comparative through lexicostatistic and reconstruction. The result of the paper indicates that Kaili dan Kulawi languages are in the same family languages with cognate percentage 62%. It indicates that those languages are in the same stock. The relationship of Kaili and Kulawi languages in the same family of languages proved by the qualitative data of sound correspondence, such as (1) l ≈ ɺ / - V#; (2) s ≈ h / - V#; (3) `g ≈ `k / - V#; (4) s ≈ x / # -; (5) ɓ ≈ b / # -; (6) J ≈ d / # -; -V#; (7) l ≈ ll / V-V; (8) J ≈ ʧ/ -V#; and (9) P ≈ B / # -.